2020
DOI: 10.1021/acsptsci.0c00169
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin-Assisted Group Therapy and Attachment: Observed Reduction in Attachment Anxiety and Influences of Attachment Insecurity on the Psilocybin Experience

Abstract: Attachment insecurity is determined early in life, is a risk factor for psychopathology, and can be measured on two separate continuous dimensions: attachment anxiety and attachment avoidance. Therapeutic changes toward more secure attachment correlate with reduction in psychiatric symptoms. Psilocybin-assisted psychotherapy has demonstrated promise in the treatment of psychopathology, such as treatment-resistant depression and substance use disorders. We hypothesized that psilocybin-assisted psychotherapy wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…A link between early relational experiences and depression is well established, with attachment difficulties suggested to partially mediate the relationship between early interpersonal trauma and depression ( Fowler et al, 2013 ). Recent research examining the relationship between insecure attachment styles and responses to individual psilocybin therapy sessions with group preparation and integrative group therapy sessions ( Stauffer et al, 2021 ), found that high attachment avoidance was associated with more intensely challenging psychedelic experiences, whereas high attachment anxiety was associated with higher levels of mystical experience in the psilocybin sessions. Furthermore, attachment anxiety was significantly reduced by the trial endpoint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A link between early relational experiences and depression is well established, with attachment difficulties suggested to partially mediate the relationship between early interpersonal trauma and depression ( Fowler et al, 2013 ). Recent research examining the relationship between insecure attachment styles and responses to individual psilocybin therapy sessions with group preparation and integrative group therapy sessions ( Stauffer et al, 2021 ), found that high attachment avoidance was associated with more intensely challenging psychedelic experiences, whereas high attachment anxiety was associated with higher levels of mystical experience in the psilocybin sessions. Furthermore, attachment anxiety was significantly reduced by the trial endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…What might look like a participant resisting the experience or not responding to psychedelics might just be a different kind of psychedelic experience. Further research is needed to better understand the quality of the psychedelic experience in cases of a weaker therapeutic alliance, e.g., is it associated with more challenging experiences ( Stauffer et al, 2021 ), amplified psychological defences or intensified transference ( Grof, 2008 )? Moreover, how might these experiences be best supported and worked with therapeutically?…”
Section: Discussionmentioning
confidence: 99%
“…Some of the potential therapeutic subjective experiences induced by psychedelics involve the transition from experiential (151,152) and emotional (88) avoidance to acceptance. Interestingly, attachment avoidance at baseline may be linked with psilocybin-related challenging experiences (153). Similarly, high neuroticism has been associated with unpleasant/anxious reactions in 3,4ethylenedioxymethamphetamine (MDMA) therapy (154).…”
Section: Fear and Threat Systemsmentioning
confidence: 99%
“…The total MEQ score was calculated as the average of all 30 items and multiplied by 20 to provide a value in a 0-100 range (MacLean et al 2012). The MEQ was previously used in both non-clinical (Haijen et al 2018;Roseman et al 2019;Kettner et al 2021) and clinical work (Barrett et al 2015;Liechti et al 2017;Schmid et al 2021;Stenbaek et al 2021;Stauffer et al 2021).…”
Section: Mystical Experience Questionnairementioning
confidence: 99%